(untitled) (Journal of Global Accounting, 2024)
The objective of this study was to examine the effect of asset management on the profitability of listed commercial banks in Nigeria. The study specifically examined the effect of current asset turnover ratio, fixed asset turnover ratio and total asset turnover ratio on profitability of DMBs in Nigeria. The study adopted the ex-post facto research design because the event under investigation had already taken place. The population of the study was made up of 13 DMBs listed on the Nigerian Exchange Group. The sample size was delimited to 10 DMBs that had their annual reports online for the period of 2014-2023. Descriptive statistics such as mean and standard deviation were used in describing the nature of the data while ordinary least square regression was used to validate the hypotheses. The results showed that: current asset turnover ratio has a significant positive effect on the return on asset; fixed asset turnover ratio has a non-significant positive effect on the return on asset and total asset turnover ratio has a non-significant negative effect on the return on asset. Based on these findings, the study recommended that: banks should optimize the management of cash, accounts receivable, inventory, and other current assets to generate more revenue and improve profitability; banks should consider reevaluating their fixed asset investment decisions and ensure that they are using their fixed assets effectively to generate more revenue and reduce costs and banks may need to balance their asset allocation to ensure that their assets are generating the desired level of revenue and profits.